The effects of ozone on bacterial growth and thiol-disulphide homeostasis in vascular graft infection caused by MRSA in rats - Ozturk,Barcin (2017)
Abstract: Purpose: To investigate the microbiological, inflammatory and oxidant effects of adjuvant ozone administration in experimental rat vascular graft infection model which has not been previously investigated. Methods: Forty adult Wistar rats were divided into Sham, Control, Vancomycin, Ozone, Vancomycin+Ozone groups. Grafts were inoculated with Methicillin-resistant Staphylococcus aureus (MRSA) strain and implanted subcutaneously. Rats were treated intraperitoneally with ozone and /or intramuscularly with vancomycin for 10 days. Grafts were evaluated by quantitative bacterial cultures. Blood samples were harvested for determination of thiol-disulphide and cytokine profiles. Results: There was no significant difference in bacterial counts between Control and Ozone Groups. In the Ozone Group median colony count was significantly higher than the Vancomycin and Vancomycin+Ozone Groups. Total thiol and disulphide levels increased and disulphide/native thiol and disulphide/total thiol ratios decreased in Ozone Group significantly. Albumin levels decreased significantly in Vancomycin and Vancomycin+Ozone Groups compared to the Sham Group. IL-1 and TNF-alpha levels significantly increased in infected rats. Decreased levels of VEGF due to infection reversed by ozone therapy in control and vancomycin groups. Conclusions: We didn't observe any benefit of the agent on MRSA elimination in our model. Likewise, effects of ozone on thiol-disulphide homeostasis and inflammatory cytokines were contradictory.